Subgingival Periodontal Pathogens Associated with Chronic Periodontitis in Yemenis - Al-Hebshi, Nezar N.; Shuga-Aldin, Hussein M.; Al-Sharabi, Ali K.; Ghandour, Ibrahim (BioMed Central (BMC), Springer Nature, 2014)
Background Subgingival microbial profile associated with periodontitis has been reported to significantly differ by geographical location. The purpose of this study was to assess the association between a panel of putative periodontal bacterial pathogens and chronic periodontitis among Yemenis. Methods Subgingival DNA samples were obtained from diseased and healthy sites of 20 non-smoking, moderate to severe chronic periodontitis subjects. Absolute counts (bacterial DNA copies per sample) and relative counts (% total bacteria) of seven periopathogenic species/genera representative of the red and orange complexes were determined using Taqman q-PCR assays. Results The q-PCR assays showed excellent linearity (R2?>?0.99) and a sensitivity of 100 copies/sample. The detection rate was 100% for all tested species/genera except for P. gingivalis and A. actinomycetemcomitans that were detected at 97.5% and 67.5%, respectively. The median log absolute counts were in the range of 2.41-6.53 copies per sample while median relative counts were in the range of 0.001-0.77%, both being highest for fusobacteria and lowest for A. actinomycetemcomitans. Significant interspecies correlations were observed. Adjusting for multiple comparisons (P?0.0063), only T. forsythia, T. denticola and P. micra maintained significant association with periodontal destruction. The latter species, however, showed the strongest association and was found in higher proportions at the periodontitis sites across all subjects (3.39 median fold increase). No significant differences were observed for P. gingivalis. Conclusions P. micra rather than P. gingivalis appears as a keystone pathogen in this Yemeni Sample. However, these findings need to be validated in a larger-scale study before they can be claimed to represent ethnic variations in pathogens association with periodontitis.